HUBUNGAN KEPERCAYAAN DIRI DENGAN PENYESUAIAN DIRI ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 2 KOTA PEKANBARU - Putri, Rizki; Nurdin, Zulkifli; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to the correlation of self confidence and self adjusment in Kindergartens Negeri Pembina 2 City of Pekanbaru. The population in this study all children aged 5-6 years in Kindergartens Negeri Pembina 2 City of Pekanbaru as many as 100 children from 5 classrooms. The tecnique of collecting data used simple random sampling. Based on the calculation using Taro Yamane formula then the sampling specified in this study is 50 children. The method used is Pearson Product Moment to see the relationship between cofidence with self adjusment. The technique of collecting data used observation sheets in the form of likert scale. The technique of analyzing data used scale test and statistic analytical by using SPSS program for windows ver.17. Based on hypothesisthere is any significant positif correlation between self confidence and personal adjusment of children aged 5-6 years in Kindergartens Negeri Pembina 2 City Of Pekanbaru. It can be known from the value of correlation coefficient of rxy = 0,538 and significance level 0,000 < 0,05. Level of relationship between self confidence and personal adjusment included in the category of being with the value of determinant coefficient of 29%, has the mening that confidence gives effect to the adjusment.Keywords : Self Adjusment, Self Confidence